A comprehensive review on Dish/Stirling concentrated solar power systems: Design, optical and geometrical analyses, thermal performance assessment, and applications. (10th February 2021) - Zayed, Mohamed E.; Zhao, Jun; Elsheikh, Ammar H.; Li, Wenjia; Sadek, S.; Aboelmaaref, Moustafa M.
Abstract: In this paper, the design criteria, opt-geometrical parameters, thermal performance analysis, thermodynamic optimization, techno-economic aspects of Solar Dish Stirling Systems (SDSS) are presented. Moreover, experimental studies that analyze the status of standalone SDSS in various countries and the operational SDSS plants are also discussed. In addition, the applications of SDSS in solar power plants, hybridization and storage, micro co-generation, water desalination, and solar cooking are extensively discussed. The reviewed results revealed the superior role of the SDSS in distributed energy systems, which have high flexibility generated capacities range between 1.0 and 38.8 kW with overall efficiencies range between 13% and 32%, and generation costs range between 0.115 and 0.256 /kWh, depending on dish concentrator size, design, and solar radiation level. Moreover, the paper also demonstrates the various novel ways to hybridize solar dish with micro gas turbines (SDMGTs) and other solar energy systems or emerging solar dish Stirling for micro co-generation systems (SDSMCOS). It is found that the SDMGTs have higher overall efficiencies of 18.35%–26.48% compared with that of SDSMCOSs which have total efficiencies of 16%–23%. Developing hybrid innovative multi-generation systems to generate electricity and heat with reasonable cost and higher thermal efficiency could help in accelerating the commercialization of dish-Stirling applications. In general, SDSS can provide promising environmentally and technically benefits, however, more efforts should be made to promote the feasibility of its commercial applications. Noteworthy discussions, important proportionalities, critical conclusions, and future strategies are also discussed as well. Highlights: The review includes the opt-geometrical and thermal analyses, and applications of solar dish Stirling systems (SDSS). Analytical and ray-tracing approaches in the receiver cavity of SDSS for optical improvement are studied. The potential contribution of simulation and optimization tools in respect of the improvement of the SDSS is identified. An economic assessment and future strategies of electricity generation in SDSS is analyzed. Recent advances of different applications based SDSS and their current challenges are discussed as well.